Closing the gap : digital equity strategies for the K-12 classroom - Thomas, Sarah, 1981-; Howard, Nicol R.; Schaffer, Regina, 1969- (International Society for Technology in Education, 2019)
"Closing the Gap: Digital Equity Strategies for the K-12 Classroom includes: examination of digital equity and the "problem of practice" for teachers and coaches; strategies for connecting the ISTE Educator and Student Standards to practice; discussion of key challenges facing teachers in today's classrooms, such as access, connectivity, limited resources, digital divide, and the homework gap; research-based vignettes from teachers who have encountered and conquered some of the challenges addressed in the book, and from edtech coaches who have implemented equity-centered innovative professional development; and concrete, evidence-based strategies for teachers"--